Forced Vibration Analysis of Functionally Graded Nanobeams - Akbaş, Şeref Doğuşcan (Imperial College Press, 2017)
In this paper, forced vibration responses of functionally graded (FG) nanobeams are presented for modified couple stress theory (MCST) with damping effect. The FG nanobeam is excited by a transverse triangular force impulse modulated by a harmonic motion. Mechanical properties of FG beam depends on the position. The Kelvin-Voigt model is considered in the damping effect. In solution of the dynamic problem, finite element method is used within Timoshenko beam theory. The obtained system of differential equations is reduced to a linear algebraic equation system and solved in the time domain by using Newmark average acceleration method. Influences of the geometry and material parameters on forced vibration responses of FG nanobeams are examined and discussed.
Akbas, Seref Doguscan/0000-0001-5327-3406
Keywords: Forced dynamic analysis; functionally graded materials; couple stress theory; nanobeams